2011
DOI: 10.1016/j.wocn.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The development of English vowel perception in monolingual and bilingual infants: Neurophysiological correlates

Abstract: The goal of this paper was to examine intrinsic and extrinsic factors contributing to the development of speech perception in monolingual and bilingual infants and toddlers. A substantial number of behavioral studies have characterized when infants show changes in behavior towards speech sounds in relation to amount of experience with these sounds. However, these studies cannot explain to what extent the developmental timeline is influenced by experience with the language versus constraints imposed by cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 88 publications
12
55
0
Order By: Relevance
“…However, no preceding MMN was found in the P-MMRs elicited by T1/T3 in newborns or by T2/T3 in 6-month-old infants. This is in line with the study conducted by Shafer et al (2011), which reported a P-MMR to English vowel contrasts without preceding MMN from 6 to 18 months of age. The P-MMR may not merely reflect the involuntary attention shifting as the P3a, but also indexes a preliminary change detection mechanism in infancy.…”
Section: Notesupporting
confidence: 93%
See 1 more Smart Citation
“…However, no preceding MMN was found in the P-MMRs elicited by T1/T3 in newborns or by T2/T3 in 6-month-old infants. This is in line with the study conducted by Shafer et al (2011), which reported a P-MMR to English vowel contrasts without preceding MMN from 6 to 18 months of age. The P-MMR may not merely reflect the involuntary attention shifting as the P3a, but also indexes a preliminary change detection mechanism in infancy.…”
Section: Notesupporting
confidence: 93%
“…The waking infants were seated comfortably on their caregivers' laps. In following similar procedures that have been used in other infant MMN studies (Morr et al, 2002;Shafer, Yu, & Datta, 2011), silent movies or cartoons were played on a monitor in front of the waking infants to engage them and minimize their movement. An experimenter entertained the infants with quiet toys whenever they lost interest in the videos.…”
Section: Methodsmentioning
confidence: 99%
“…Although our P2 window clearly falls outside the P1 time-window (Fig. 1), auditory P1 latencies in response to vowels have been reported to extend into our P2 time-window (Shafer et al, 2011). However, other studies using spoken word stimuli observed similar P1 latencies as here (100 ms; Mills & Sheehan, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…ERP components can be roughly divided into early components reflecting perceptual processes modulated by attention (up to $300 ms after stimulus onset), and later components reflecting more conscious stimulus processing influenced by voluntary allocation of attention and cognitive strategies ($300-600 ms after stimulus onset). Importantly, studies of early ERPs in response to (speech) sounds have shown that maturation of the auditory cortex is directly liked to language learning and that the rate of maturation differs in monolingual and bilingual children (Kuhl et al, 2008;Shafer, Yu, & Datta, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may be a developmental issue. The negative MMR may be equivalent to the adult MMN (He et al 2007, 2009; Shafer et al 2010, 2011). With increasing age, the negative MMR becomes larger in amplitude and earlier in latency (Shafer et al 2000, 2010; Morr et al 2002).…”
Section: What Is the Mmn?mentioning
confidence: 99%